ANALISIS KEKERASAN, STRUKTUR MIKRO MATERIAL RING PISTON 5MX-E160-10 DENGAN PROSES HEAT TREATMENT - Sri Widodo; Kun Suharno; Hasyim Tri Gustomo; Fuad Hilmy (Universitas Tidar, 2018)
Now, many of piston ring parts have been on the market. The products are often encountered are the 5MX-E160-10 series piston ring and the SLW-E1603-20 series piston ring which have different qualities. In this study, the hardness of the two piston ring products was analyzed by heat treatment. The heat holding time was varied 15 minutes, 30 minutes and 45 minutes at 8000C and the quenching media of SAE 40 oil. The results of the hardness of the 5MX-E160-10 series raw material were 105.97 HRB and the highest hardness value after treatment decreased 34.02% were 71.95 HRB. While the hardness value of the SLW-E160-20 series raw material were 90.26 HRB and after the heat treatment has decreased by 19%, were 71.26 HRB. The best microstructure test results were found at the 30 minute holding time series 5MX-E160-10 with a temperature of 8000C and the quenching media of SAE 40 oil. In addition, the results showed that the longer holding time in the SLW-E1603-20 series resulted in decreased hardness values.